Improving Midwives Competence in Postpartum Depression Screening through EPDS Training - Christiana, Indah; Wahyuningsih, Indah; Novitasari, Erlin (Universitas Aisyiyah Yogyakarta, 2025)
Postpartum depression represents preventable challenges and has a significant impact on both mother and baby. Depression affects over ten percent of individuals during the perinatal period. The prevalence of reported cases of postpartum depression statistically appears low, but in reality there are still cases in the community. The cause of the high obstacle is that many midwives have not been able to apply due to lack of knowledge and skills in using EPDS. This study aims to determine the effect of postpartum depression screening training using EPDS on the knowledge and skills of midwives in detecting postpartum depression. Pre-experimental research type and one group pretest posttest design. The population was all midwives at Genteng Hospital as many as 31 midwives with sampling using total sampling. Analysis of the data was performed using SPSS for Windows (Version 25), employing the Wilcoxon signed-rank test and multiple logistic regression. The analysis yielded a significant increase in knowledge scores, with a mean difference of 38.71 and skills by 88.533 after training. Multivariate results showed that age, education, nursing field, did not affect knowledge and skills, while length of work did not affect knowledge but affected skills by 14, 107 times. Midwives can be more proactive in screening for postpartum depression using EPDS as an early prevention step, so as to identify the risk of postpartum depression more precisely.